2023
DOI: 10.3390/ijerph20021231
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Level Analysis of Individual and Neighborhood Factors Associated with Patient Portal Use among Adult Emergency Department Patients with Multimorbidity

Abstract: Background: Patient portals tethered to electronic health records (EHR) have become vital to patient engagement and better disease management, specifically among adults with multimorbidity. We determined individual and neighborhood factors associated with patient portal use (MyChart) among adult patients with multimorbidity seen in an Emergency Department (ED). Methods: This study adopted a cross-sectional study design and used a linked database of EHR from a single ED site to patients’ neighborhood characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Literature about ED portal use is sparse, which is problematic because the ED represents the primary care environment for many medically underserved and underinsured patients who use portals at lower rates despite equally or more complex care needs . Preliminary studies suggested that portal access initiated in the ED, especially among patients experiencing houselessness, is associated with increased clinic attendance and care adherence . Improved care adherence may follow from the ability to manage care asynchronously by scheduling appointments, messaging care teams, and reviewing results, which extends the care network beyond the doors of the ED .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature about ED portal use is sparse, which is problematic because the ED represents the primary care environment for many medically underserved and underinsured patients who use portals at lower rates despite equally or more complex care needs . Preliminary studies suggested that portal access initiated in the ED, especially among patients experiencing houselessness, is associated with increased clinic attendance and care adherence . Improved care adherence may follow from the ability to manage care asynchronously by scheduling appointments, messaging care teams, and reviewing results, which extends the care network beyond the doors of the ED .…”
Section: Introductionmentioning
confidence: 99%
“… 6 , 11 Preliminary studies suggested that portal access initiated in the ED, especially among patients experiencing houselessness, is associated with increased clinic attendance and care adherence. 12 , 13 , 14 Improved care adherence may follow from the ability to manage care asynchronously by scheduling appointments, messaging care teams, and reviewing results, which extends the care network beyond the doors of the ED. 15 , 16 More acutely, real-time ED portal access might facilitate sooner identification of critical results or empower patients to detect missed incidental findings.…”
Section: Introductionmentioning
confidence: 99%
“…8 Particularly, in the US, the 21st Century Cures Act has mandated the sharing of clinical documentation with patients and families. [9][10][11][12] While many studies have yielded important lessons for successful portal implementations in primary and acute care settings (e.g., the importance of engaging patients and families and clinical workflows), 8,[13][14][15] in the mental health domain, it is still relatively uncommon to share health information with patients and families due to stigma and impact on therapy. 16 Despite growth in this area, [17][18][19][20] there has been significant concern and apprehension around sharing notes with patients.…”
Section: Introductionmentioning
confidence: 99%